Meeting recommendations for weekly physical activity in adult population in the southern Bohemian region - Emil Řepka; Zdeněk Šebrle; Karel Frömel; František Chmelík; Zuzana Vašíčková (Palacký University Olomouc, 2011)
BACKGROUND: The characteristics of physical activity (PA) of inhabitants show a great variability depending on their national, cultural and environmental conditions. Therefore, even on the regional level in each state one can expect certain specifics in physical activity performance and lifestyle. OBJECTIVE: The main aim of the study was to analyze the associations between physical activity, body mass index, sex and other characteristics of the inhabitants in the Southern Bohemian region in regard with meeting recommendations for physical activity and provide thus information that can help to enhance healthy lifestyle in this region. METHODS: Using the standardized IPAQ questionnaire (long administrative version) in 2005-2009, we collected data on physical activity in 1123 randomly selected adult respondents (628 women, 495 men) from Southern Bohemian region. RESULTS: The biggest difference in meeting PA recommendations was found in vigorous PA (χ 2 = 35.42, p < 0.001) in women (p = 0.018) and in men (p = 0.009) with different weight. Bigger chance to meet the weekly PA recommendations is in people who live in smaller towns or villages, or in those who own a dog. CONCLUSIONS: In opposition to results of similar studies, positive associations between meeting PA recommendations and participation in organized PA, smoking, sex and respondents' age were not proved. In total weekly PA no signific ant differences were found between men and women. These differences were found in the structure of PA. PA in the inhabitants of the Southern Bohemian region analyzed in this study is similar to results of other studies carried out on the national level.